The International Criminal Court - Glasius, Marlies (Routledge Advances in International Relations and Global Politics, 2006)
A new examination of the International Criminal Court (ICC) from a political science and international relations perspective. It describes the main features of the court and discusses the political negotiations and the on-going clashes between those states who oppose the court, particularly the United States, and those who defend it. It also makes these issues accessible to non-lawyers and presents effective advocacy strategies for non-governmental organizations. It also delivers essential background to the place of the US in international relations and makes a major contribution to thinking about the ICC's future. While global civil society does not deliver global democracy, it does contribute to more transparent, more deliberative and more ethical international decision-making which is ultimately preferable to a world of isolated sovereign states with no accountability outside their borders, or exclusive and secretive state-to-state diplomacy. This book will be of great interest to students and scholars of international relations, international law, globalization and global governance.